Atypical nature of coronary artery disease in women: a proposal for measurement and classification - Viviana Marycel Céspedes Cuevas (Universidad Nacional de Colombia, 2015)
Objective: To identify subgroups of women with Acute Coronary Syndrome according to symptom experience: perception, evaluation and response, based on the Symptom Management Conceptual Model. Methodology: Quantitative, descriptive, exploratory, cross-sectional study. The sample was made of 380 women positively diagnosed with Acute Coronary Syndrome, hospitalized in two institutions in Bogotá, Colombia. A measurement instrument was designed and validated. Results: Final instrument was made of 37 items that reported content validity, scale validity, discriminant validity, and construct validity. A Cronbach's Alpha coefficient of 0,76 was obtained, which guarantees homogeneity in the measurement according to the Maximum Validity-Maximum Reliability Model. A total of 11 subgroups of women with Acute Coronary Syndrome were identified, those were characterized by atypical coronary heart disease symptomatology, evaluation processes related to extra-cardiac causes and inadequate symptom management strategies. It was possible to demonstrate that psychosocial factors, previous coronary heart disease and delays were variables making a significant influence on the components of symptom experience. Conclusions: Women with Acute Coronary Syndrome, belonging to the 11 subgroups that were identified and studied, showed atypical symptoms. The instrument designed features a proven psychometric quality; it was valid, reliable, and useful for clinical research and practice.